Inter-American system: stages and development of relations between the United States and Latin America - Goliney Vladimir (Латиноамериканский исторический альманах)
The article explores the evolution of the Inter-American Sys-tem from the 19th century until 2024. It describes some char-acteristics of this system and identifies several stages in its development, based on differences in the perspectives of politicians in the Western Hemisphere regarding security issues, trade cooperation, and the international environment. The theme of security and economic collaboration runs like a re-curring theme throughout the more than 200-year history of U.S. foreign policy engagement with Latin American and Car-ibbean countries, providing a sense of continuity in the stages of Inter-American cooperation development. This is illustrat-ed by examples such as the Spanish American Congresses of 1826–1865, Pan-American Conferences of 1889–1954, and Summits of the Americas from 1994–2022. At each of these phases, there has been a mutual adjustment in the foreign policies of Western Hemisphere countries. In 2023, the Biden administration launched several new initiatives aimed at unit-ing several Latin American countries, coinciding with Brazil’s efforts to establish its own macro-regional entity within the context of the changing international relations system. These developments highlight the fact that the Western Hemisphere has two distinct roots: Latin America and North America. For a long time, North America has dominated, allowing the USA to shape the Inter-American system based on its own principles. However, the current trends of deglobalization and the fragmentation of the global landscape are allowing Latin American countries to propose their own ideas for shaping this system in the future. Based on these trends, the author proposes several possible scenarios for the evolution of the Inter-American system.